Breastfeeding versus free distribution of infant formulas by the Public Health System - Flávia Galvão Cândido; Brunnella Alcântara Chagas de Freitas; Rita de Cássia Santos Soares; Jersica Martins Bittencourt; Daniela Neves Ribeiro; Dayane de Castro Morais; Camilla de Freitas Niquine; Sarah Aparecida Vieira Ribeiro; Raquel Maria Amaral Araújo; Bruna Romano Zucchetto; Taimã de Castro Carvalho; Isabela Carvalho Rezende (Einstein (São Paulo), 2021)
ABSTRACT Objective: To characterize the situation of breastfeeding and the adequacy of prescription of infant formulas to infants assisted by a secondary care program of the Public Health System. Methods: This is a cross-sectional study with analysis of medical records of 350 infants from zero to 6 months, followed up between February to April 2019. Results: The possibility of breastfeeding was present in 97.0% of mothers and no infant presented an acceptable medical condition for proscription of breastfeeding. Despite this, only 47.2% of cases were on exclusive breastfeeding before being referred to the program. Regarding the reasons for the introduction of infant formulas, complementation to breast milk was the most present (75.8%), followed by mothers returning to the job market (20.1%). The general rates of inadequacy of those prescribed were 65% before arriving at the program, increasing to 69% (standard formulas) and 80% (formulas for special purposes) during follow-up. Conclusion: The low rate of exclusive breastfeeding and the indiscriminate prescription of infant formulas are a concern for damage to maternal-child healthcare and sound finances of the Public Health System.